2014
DOI: 10.1016/j.bpj.2013.11.4505
|View full text |Cite|
|
Sign up to set email alerts
|

Membrane Fluctuations Destabilize Clathrin Protein Lattice Order

Abstract: We develop a theoretical model of a clathrin protein lattice on a flexible cell membrane. The clathrin subunit is modeled as a three-legged pinwheel with elastic deformation modes and intersubunit binding interactions. The pinwheels are constrained to lie on the surface of an elastic sheet that opposes bending deformation and is subjected to tension. Through Monte Carlo simulations, we predict the equilibrium phase behavior of clathrin lattices at various levels of tension. High membrane tensions, which corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 85 publications
1
13
0
Order By: Relevance
“…The magnitude of changes in membrane properties caused by mycolactone could, in principle, influence the activity of membrane-embedded proteins [ 49 ]. Previous studies have addressed how changes in membrane elastic properties can affect glucose transporters [ 50 ], the stability of voltage sensor segments [ 51 ], mechano-sensitive channels of large conductance [ 52 ], and clathrin protein ordering [ 53 ]. However, the most likely connection between membrane association and Sec61 inhibition is that trafficking to the endoplasmic reticulum could facilitate mycolactone binding to the Sec61 translocon.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of changes in membrane properties caused by mycolactone could, in principle, influence the activity of membrane-embedded proteins [ 49 ]. Previous studies have addressed how changes in membrane elastic properties can affect glucose transporters [ 50 ], the stability of voltage sensor segments [ 51 ], mechano-sensitive channels of large conductance [ 52 ], and clathrin protein ordering [ 53 ]. However, the most likely connection between membrane association and Sec61 inhibition is that trafficking to the endoplasmic reticulum could facilitate mycolactone binding to the Sec61 translocon.…”
Section: Discussionmentioning
confidence: 99%
“…Previous simulations on budding of nanoscale particles led to important insights but did not consider the effect of GPs ( [24][25][26][27][28][29][30][31]), although budding directed by GP adsorption or capsid assembly have been the subject of continuum theoretical modeling [32][33][34]. The formation of clathrin cages during vesicle secretion, a process which bears similarities to viral budding, has also been the subject of modeling studies [35][36][37][38]. Most closely related to our work are previous simulations on the assembly and budding of 12-subunit capsids, which found that membrane adsorption can lower entropic barriers to assembly [39,40] and that membrane microdomains can facilitate assembly and budding [41].…”
Section: Introductionmentioning
confidence: 99%
“…These experimental studies are complimented by the modeling work by Walani et al which suggests that an increase in tension should lead to smaller clathrin coat in order to match experimentally observed shapes observed in mammalian and yeast cells 17 . In addition, stochastic models have given fundamental insights into clathrin self-assembly 18,19 and dynamic rearrangements in clathrin lattices 2022 . In particular, curvature generation by indentation has been shown to promote solid to fluid phase transition in a planar clathrin lattice 21 .…”
Section: Introductionmentioning
confidence: 99%